2021
DOI: 10.3390/foods11010066
|View full text |Cite
|
Sign up to set email alerts
|

Different Thermal Treatment Methods and TGase Addition Affect Gel Quality and Flavour Characteristics of Decapterus maruadsi Surimi Products

Abstract: Decapterus maruadsi surimi products were prepared using the thermal treatment methods of boiling (BOI), steaming (STE), back-pressure sterilization (BAC), roasting (ROA), microwaving (MIC), and frying (FRI), respectively. The effect of glutamine transaminase (TGase) addition was also investigated. The moisture distribution, water retention, microstructure, color, fracture constant, protein secondary structure, chemical forces, and flavor components of each sample were determined. The differences in gel and fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 67 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…The addition of MTGase significantly reduced ionic bonds and hydrogen bonds ( p < .05) (Figure 4a, b). MTGase could significantly enhance the cross‐linking within protein and decrease interactions of hydrogen and ionic linking (Li et al, 2022). The groups, required to form hydrogen and ionic bonds, were catalyzed to form covalent bonds by MTGase, which might decrease ionic and hydrogen bonds (Hu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of MTGase significantly reduced ionic bonds and hydrogen bonds ( p < .05) (Figure 4a, b). MTGase could significantly enhance the cross‐linking within protein and decrease interactions of hydrogen and ionic linking (Li et al, 2022). The groups, required to form hydrogen and ionic bonds, were catalyzed to form covalent bonds by MTGase, which might decrease ionic and hydrogen bonds (Hu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophilic carboxyl group of polyphenols might increase hydrophobic interactions by competing for the hydrophilic group of myofibrillar proteins (Hu et al, 2018; Sharma et al, 2022). Hydrophobic interactions were significantly decreased in surimi gels with the addition of MTGase ( p < .05), because protein cross‐linking induced by MTGase formed polymers and had a negative effect on the exposure of hydrophobic residues (Li et al, 2022). MTGase could promote the cross‐linking between the free γ‐carboxy‐amide group of glutamine residues and a number of primary amines (including the α‐ and ε‐amino groups of lysine) (Jia et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin has been widely produced by hydrolyzing tissues such as animal skin and bone or by recombinant expression of microorganisms, and it can form stable hydrogels after cross-linking using TGase (Wang et al, 2017;Sonaye et al, 2022;Andreazza et al, 2023). TGase is a safe food additive that has been widely used to improve the flavor, texture, and appearance of meat products (Li et al, 2021;Chen Y. et al, 2023). In this study, we combined gelatin and three food-grade hydrocolloidal materials SA, CS, and GG to obtain bio-inks.…”
Section: Discussionmentioning
confidence: 99%
“…TGase is able to cross-link better with proteins, leading to structural changes that result in improved water retention, and are therefore widely used in meat gels. (Li et al, 2022b) found that when 0.4% TGase was added to balsa fish balls, the gel strength and water retention of the fish balls could be improved, and the material ratios for optimum water rentention were also determined by response surface optimisation metthod. (Zhao, 2023) also did a similar study on salmon surimi gel.…”
Section: Biotechnologymentioning
confidence: 99%